Folic acid, either solely or combined with L‐citrulline, improves NO signaling and ameliorates chronic hypoxia‐induced pulmonary hypertension in newborn pigs - Matthew Douglass; Anna Dikalova; Mark R. Kaplowitz; Yongmei Zhang; Gary Cunningham; Marshall Summar; Candice D. Fike (Physiological Reports, 2021)
Abstract Concomitant with developing pulmonary hypertension (PH), newborn piglets exposed to chronic hypoxia develop pulmonary vascular NO signaling impairments. PH is reduced and NO signaling is improved in chronically hypoxic piglets treated with the NO‐arginine precursor, L‐citrulline. Folic acid positively impacts NO signaling. We evaluated whether the effect on NO signaling and PH is greater using co‐treatment with folic acid and L‐citrulline than either alone. From day 3 to day 10 of hypoxia, piglets were treated solely with folic acid, solely with L‐citrulline, or co‐treated with both. Catheters were placed to measure in vivo hemodynamics. NO production was measured in vitro in dissected pulmonary arteries. Compared to normoxic piglets, pulmonary vascular resistance (PVR) was elevated and NO production was reduced in untreated hypoxic piglets. Regardless of treatment strategy, PVR was less in all three treated groups of hypoxic piglets when compared to the untreated hypoxic group. In addition, for all three groups of treated hypoxic piglets, NO production was higher than the untreated group. Improvements in PVR and NO production did not differ between piglets co‐treated with folic acid and L‐citrulline and those treated solely with either. Thus, the impact on NO production and PVR was not augmented by combining folic acid and L‐citrulline treatments. Nonetheless, treatment with folic acid, either singly or when combined with L‐citrulline, increases NO production and inhibits PH in chronically hypoxic newborn piglets. Folic acid merits consideration as a therapy for PH in human infants with chronic heart and lung conditions that are associated with chronic hypoxia.